A human model of Buruli ulcer: Provisional protocol for a Mycobacterium ulcerans controlled human infection study - Muhi, Stephen; Marshall, Julia L.; O'Brien, Daniel P.; Johnson, Paul D.R.; Ross, Gayle; Ramakrishnan, Anand; Mackay, Laura K.; Doerflinger, Marcel; McCarthy, James S.; Jamrozik, Euzebiusz; Osowicki, Joshua; Stinear, Timothy P. (Wellcome open research, 2024)
Critical knowledge gaps have impeded progress towards reducing the global burden of disease due to Mycobacterium ulcerans , the cause of the neglected tropical disease Buruli ulcer (BU). Development of a controlled human infection model of BU has been proposed as an experimental platform to explore host-pathogen interactions and evaluate tools for prevention, diagnosis, and treatment. We have previously introduced the use case for a new human model and identified M. ulcerans JKD8049 as a suitable challenge strain. Here, we present a provisional protocol for an initial study, for transparent peer review during the earliest stages of protocol development. Following simultaneous scientific peer review and community/stakeholder consultation of this provisional protocol, we aim to present a refined protocol for institutional review board (IRB) evaluation.